Management of Corporate Business Process Cost Performance Based on Key Costs Data - Vizgunov, Alexander N.; Trifonov, Yuri V. (International Journal of Economics and Financial Issues, 2017)
One of the most complex problems of implementing corporate process-based management includes arrangements for accounting and analysis of costs related to business process execution. Methods conventionally used to these ends cannot be leveraged in terms of business processes whose cost performance changes dynamically, which is particularly customary for companies in emerging markets. The methods proposed by this article authors are only based on accounting and analysis of most important key costs. In reliance on key costs, one develops an indirect costs exact distribution model, which indirect costs are related to the execution of various business processes. Key costs data is also used to analyze alternatives of cost reduction and risk minimization. This paper offers criteria for qualifying costs as key costs. Fundamental principles have been determined for developing an activity-based costing model based on key costs data, and trends in analysis of key costs have been established. Keywords: Business Process Management, Cost Analysis, Activity-Based Costing. JEL Classifications: D24, M4